High energy resolution measurements of the radiative decay of double K-shell vacancies in 20 ≤ Z ≤ 29 elements bombarded by fast C and Ne ions. (July 2015) - Dousse, J-Cl; Maillard, Y-P; Berset, M; Castella, D; Hoszowska, J; Kavčič, M; Kobal, M; Mauron, O.; Muehleisen, A.; Raboud, P.-A.; Rzadkiewicz, J.; Tökési, K; et al.
Synopsis: We report on high energy resolution measurements of the Kα hypersatellite x-ray spectra of Ca, V, Fe and Cu induced by impact with 144 MeV C and 180 MeV Ne ions.